Pathologoanatomic appearance of dog dirofilariasis caused by Dirofilaria immitis - Сорокова, В. В. (Scientific Progress & Innovations, 2012)
The article contains materials about the pathologoanatomic changes of dog dirofilariasis caused by Dirofilaria immitis. Pathomorphological researches showed emaciation, anemia mucous membranes, protein steatosis, nefrozonefrit, venous hyperemia and pulmonary edema, hypertrophy and acute enlargement in the right part of a heart, hydrothorax, ascites and gematurіa. Also are shown the changes non-specific for disease: catarrhalhemorrhagic gastroenterokolit and hemorrhagic dіatez. In the heart, lungs and pulmonary arteries of dogs, died of dirofilariasis, found mature parasites Dirofilaria immitis, which led to the death of the animals.